Effectiveness of a task-oriented training on occupational performance, functional independence, and fatigue in children with childhood cancer: a randomized-controlled trial/ Eficácia de um treino com tarefas orientadas para o desempenho ocupacional, independência funcional e fadiga em crianças com câncer na infância: um estudo aleatório controlado - Kolit, Zeynep; Şahin, Sedef; Davutoğlu, Ceren; Huri, Meral (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Objective: The objective of the study is to explore the effectiveness of task-oriented training (TOT) on occupational performance, functional independence, and fatigue of children with cancer. Method: Two hundred and thirteen children (101 females, 112 males) with cancer were randomized to experimental (n = 112; 9.53±2.23 years) or control (n = 101; 7.93±1.98 years) groups. The experimental group received a TOT together with a conventional occupational therapy (COT), while the control group received only a COT. Both groups received 20 sessions of therapy. The outcomes regarding occupational performance via the Canadian Occupational Performance Measure, functional independence via the Functional Independence Measure for Children and fatigue via the Visual Analog Scale were evaluated by the blind evaluators before and after the interventions in the hospital setting.Results: The occupational performance and satisfaction (p<0.001) scores showed statistically significant differences in the experimental group compared to the control group (p<0.01). A statistically significant improvement was determined in functional independence for both groups (p< 0.001). The experimental group indicated a significant reduction in fatigue (p values for fatigue before, during, after activity, morning and evening: p< 0.001) and in the control group (P values for fatigue all situation: p< 0.05). Conclusion: The TOT seems to ensure more beneficial effects in increasing occupational performance, improving functional independence in daily activities, and decreasing fatigue at the early phases of inpatient treatment of childhood cancer.